Răspuns :
f(x) = x³ -12x , cu x ∈R
f'(x) = 3x² -12 = 3 · ( x² - 4) = 3·( x -2) ·( x +2)
rad. derivatei f'(x) = 0
3· ( x -2) ·( x +2) = 0 ⇒ rad x₁ = 2 ; x₂ = - 2 derivatei
Studiu SEMN :
x - ∞ - 2 2 +∞
---------------------------------------------------------
f ' + 0 --- 0 +
--------------------------------------------------------
f mont. cres m. des. monoton crescatoare
MAX min
A ( - 2 ; 16 ) B ( 2 ; -16)
f'(x) = 3x² -12 = 3 · ( x² - 4) = 3·( x -2) ·( x +2)
rad. derivatei f'(x) = 0
3· ( x -2) ·( x +2) = 0 ⇒ rad x₁ = 2 ; x₂ = - 2 derivatei
Studiu SEMN :
x - ∞ - 2 2 +∞
---------------------------------------------------------
f ' + 0 --- 0 +
--------------------------------------------------------
f mont. cres m. des. monoton crescatoare
MAX min
A ( - 2 ; 16 ) B ( 2 ; -16)